Model Framework for Development of Biodiversity Information Systems. (July 2019) - Budiman, Edy; Puspitasari, Novianti; Wati, Masna; Haviluddin,; Rahim, Robbi
Abstract: The aim of the study was to design a framework for developing bioinformatics resource information systems using the Model-View-Controller (MVC) design pattern. Research contributions generate a framework as an approach model for the development of Biodiversity Information Systems which aims to improve computational capabilities and management of biodiversity data resources for the use of public information clusters. This product combines component capabilities (View Controller Model (MCV), Object Relational Mapping (ORM) and ICBN Nomenclature Taxonomy) with reusable resources. The results of the study have produced a special prototype in the form of a Framework in the Development of Bioinformatics resource information systems that can be accessed online in the site: http://borneodiversity.org/index.